2021
DOI: 10.1038/s41598-021-90183-w
|View full text |Cite
|
Sign up to set email alerts
|

Semantic and spatial congruency mould audiovisual integration depending on perceptual awareness

Abstract: Information integration is considered a hallmark of human consciousness. Recent research has challenged this tenet by showing multisensory interactions in the absence of awareness. This psychophysics study assessed the impact of spatial and semantic correspondences on audiovisual binding in the presence and absence of visual awareness by combining forward–backward masking with spatial ventriloquism. Observers were presented with object pictures and synchronous sounds that were spatially and/or semantically con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 72 publications
2
16
0
Order By: Relevance
“…Additionally, there was an interaction effect between the semantic and spatial congruences where the effect of the semantic congruence on the audiovisual binding was increased when the sound was presented bilaterally (Delong & Noppeney, 2021). In experiment 2, they found a significant positive effect of semantically congruent stimuli on picture identification (in line with previous studies such as Chen and Spence (2010)).…”
Section: Semantic Congruence and Multisensory Integrationsupporting
confidence: 83%
See 4 more Smart Citations
“…Additionally, there was an interaction effect between the semantic and spatial congruences where the effect of the semantic congruence on the audiovisual binding was increased when the sound was presented bilaterally (Delong & Noppeney, 2021). In experiment 2, they found a significant positive effect of semantically congruent stimuli on picture identification (in line with previous studies such as Chen and Spence (2010)).…”
Section: Semantic Congruence and Multisensory Integrationsupporting
confidence: 83%
“…In experiment 2, they found a significant positive effect of semantically congruent stimuli on picture identification (in line with previous studies such as Chen and Spence (2010)). Experiment 2 also found a significant interaction effect of semantic and spatial congruences (as in experiment 1) but only for the visible conditions (conditions where the participant identified that they saw and recognized the image) as opposed to the invisible conditions (where the participants reported that they could not identify the image that was presented) (Delong & Noppeney, 2021). Ultimately, this study further reinforces the impact that semantic congruency has on our multisensory integration and demonstrates that it is related to other factors such as spatial congruency.…”
Section: Semantic Congruence and Multisensory Integrationmentioning
confidence: 69%
See 3 more Smart Citations